WEDANG KACANG MERAH MENINGKATKAN HEMOGLOBIN, HEMATOKRIT, DAN ERITROSIT IBU HAMIL DENGAN KASUS ANEMIA - Handayani, Wahyu; Anwar, M. Choirul; Santjaka, Aris (Poltekkes Kemenkes Bandung, 2025)
Effective nutritional management is needed because anemia during pregnancy has a major impact on the mother and fetus. Iron, folic acid, and vitamin B are abundant in red beans and play a role in erythrocytes, hemoglobin, and hematocrit production. Vitamin B and folic acid promote the development of red blood cells to increase the levels of hemoglobin, hematocrit, and erythrocytes in pregnant women.Researchers created a red bean drink.This study aimed to determine the effect of red bean drink on hemoglobin, hematocrit, and erythrocyte levels in pregnant women.This study used a quasi-experimental design with pretest-posttest with control group design,consisting of 2 groups.The population was 33 pregnant women who experience anemia in the Garung Health Center Working Area taken by purposive sampling.The data collected are hemoglobin, hematocrit, and erythrocyte levels. The intervention was the consumption of 100 g of red bean drink for 14 days.Analysis used Wilcoxon and Paired Sample Test. The average hemoglobin before and after intervention in the intervention group was 10.14 and 11.62, and in the control group,10.64 and 11.05.The average hematocrit of the intervention group was 29.11 and 30.38, and in control group, it was 32.92 and 33.08.The average erythrocytes before and after intervention in intervention group were 3.38 and 3.81,and in the control group,3.72 and 3.95. There was a significant effect of red bean drink on increasing hemoglobin (p=0.040), hematocrit (p=0.000), and erythrocytes (p=0.007). Consuming 100 grams of red bean drink for 14 days effectively increased hemoglobin, hematocrit, and erythrocyte levels in pregnant women with anemia.